1998
DOI: 10.1139/w98-119
|View full text |Cite
|
Sign up to set email alerts
|

Fungal melanins: a review

Abstract: The relationship of polyketide melanogenesis molecular biology to that of nonmelanin-producing pathways in a wide range of fungi and other organisms is discussed. Analytical methods and fundamental properties of melanins are discussed and fungal melanin properties are compared with those of animal and bacterial melanins. The enzymatic degradation of melanins by lignin peroxidases is described.Key words: fungal melanin, polyketide melanin, DHN melanin, melanin degradation, melanin properties, melanin analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
351
1
31

Year Published

2001
2001
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 602 publications
(385 citation statements)
references
References 168 publications
2
351
1
31
Order By: Relevance
“…Melanin is a condensed, randomly arrayed, aromatic pigment that is located in the cell wall or extracellular matrix of fungi (161)(162)(163). It broadly protects fungi from an array of environmental stresses, including extreme heat and cold, drought, UV radiation, high salinity, heavy metals, and anthropogenic pollutants (164)(165)(166)(167)(168)(169)(170).…”
Section: Stress Tolerancementioning
confidence: 99%
See 1 more Smart Citation
“…Melanin is a condensed, randomly arrayed, aromatic pigment that is located in the cell wall or extracellular matrix of fungi (161)(162)(163). It broadly protects fungi from an array of environmental stresses, including extreme heat and cold, drought, UV radiation, high salinity, heavy metals, and anthropogenic pollutants (164)(165)(166)(167)(168)(169)(170).…”
Section: Stress Tolerancementioning
confidence: 99%
“…As a result, tissues of melanized fungi are particularly recalcitrant (46,177,178). Accordingly, it has been suggested that melanin contributes to C storage in soils (5), eventually accumulating as humic material (163,177,179). In consideration of these properties, Koide et al (42) proposed melanin production as a fungal trait that may form a direct link between environmental stress and ecosystem function.…”
Section: Stress Tolerancementioning
confidence: 99%
“…formation of resting bodies called sclerotia [24]) or stress response (i.e. mycelia melanization [25,26]). …”
Section: Introductionmentioning
confidence: 99%
“…The physiological properties of conidia have drawn the attention of biologists and breeding experts. Butler and Day (1998) reported that conidia in A. niger showed strong tolerance to UV-rays due to the presence of melanin in conidia. Similar results were found by Liu et al (2014).…”
Section: Discussionmentioning
confidence: 99%